To Compare the Efficacy of Heated Humidified High-Flow Nasal Cannula and Continuous Positive Airway Pressure in Post-Extubation Period in VLBW Infants. (8th August 2017) - Garg, Bhawan Deep; Bajaj, Naveen; Sharma, Deepak
Abstract: Objective: The objective of this study was to compare efficacy of continuous positive airway pressure (CPAP) and heated humidified high-flow nasal cannula (HHHFNC) as noninvasive respiratory support in post-extubation period in very low birth weight (VLBW) infants. Method: This retrospective study enrolled 136 neonates, ≤32 weeks gestation and ≤1500 grams birth weight, requiring noninvasive respiratory support during post-extubation period. Results: There was no significant difference in post-extubation failure in HHHFNC group when compared with CPAP group ( p > 0.05) but post-extubation complication was significantly higher in CPAP group ( p < 0.05) including nasal septal trauma and pneumothorax. Conclusions: In neonates ≤32 weeks of gestational age, HHHFNC showed similar efficacy, and better safety profile than nasal-CPAP when used during post-extubation period for respiratory support.